2020
DOI: 10.7759/cureus.6648
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Small Cell Lung Cancer in King Abdulaziz University Hospital, Jeddah, Saudi Arabia

Abstract: Background Lung cancer is estimated to be 12% of all new cases of cancer. It is one of the most common cancers in men and women, and it is the main cause of cancer-related death in the United States of America. More than 90% of small cell lung cancer (SCLC) patients are elderly, with a current or past history of smoking. In Saudi Arabia, lung cancer incidence is low as compared to the global incidence. In 2013, the age-standardized ratio (ASR) was 1.8 per 100,000 for females and 5.5 per 100,000 for males. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Most patients’ overall survival is less than 5 years whom were diagnosed at advanced stage [ 26 ]. Existing treatments extend the survival of part of patients with lung adenocarcinoma, but the overall curative effect is not so good, especially in the advanced cases [ 27 , 28 ]. The shortage of effective prognostic biomarkers to guide therapy is one of the reasons for the poor prognosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients’ overall survival is less than 5 years whom were diagnosed at advanced stage [ 26 ]. Existing treatments extend the survival of part of patients with lung adenocarcinoma, but the overall curative effect is not so good, especially in the advanced cases [ 27 , 28 ]. The shortage of effective prognostic biomarkers to guide therapy is one of the reasons for the poor prognosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Saudi Arabia found that the median duration of survival for patients with small cell lung carcinoma was 6.4 months. 5 Lung cancer is one of the leading causes of death worldwide, and it is ranked as the first cause of death in more than 100 countries around the world. 6 The five-year survival rate of lung cancer is only around 14%, 7 however, when it is diagnosed at early age, the overall survival rate will increase in around 50% of the patients, nevertheless, only small percentage of patients are diagnosed at early stage.…”
Section: Introductionmentioning
confidence: 99%